The effect of using the six hats strategy on the academic achievements of first-grade students and their flexible understanding - RababAbd Hussein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The current research delves into the six hats strategy and it's impact on the mathematical results and the flexible conceptions of the first grade class of the mathematical subject. The researcher focuses on the two chapters " fifth and sixth ones" that are specified for the first grade students of the mathematics curriculum, the second part of the academic year( 2018-2019) the vision "2018" .     The researcher adopted the experimental design" partial control" for the two groups of the experimental research of the " post test". The subjects of the two groups of the present research include" intelligence, age by month& the previous information". The "experimental research" and the "control group" subjects that given by only one teacher in according of the previous prepared plans. To measure the level of the students, aspecific test conduct which consist of " 25 items" distributed on six levels of " Bloom" classification,namely; "knowledge,comprehension,application,analysis,composition and evaluation" of the cognitive domain. To make sure the correctness of the results;the test offered to a certain judges and for proving its accuracy, the " Cronbach" is used.   The outcome was (0,71) while the measurable variables " the flexible conception" ,the researcher used an already studied test consist of " 40 tests items".